2016
DOI: 10.4196/kjpp.2016.20.6.621
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus caseistrain C1 attenuates vascular changes in spontaneously hypertensive rats

Abstract: Hypertension can be caused by various factors while the predominant causes include increase in body fluid volume and resistance in the circulatory system that elevate the blood pressure. Consumption of probiotics has been proven to attenuate hypertension; however, the effect is much strain-dependent. In this study, a newly isolated Lactobacillus casei (Lb. casei) strain C1 was investigated for its antihypertensive properties in spontaneously hypertensive rats (SHR). Lactic acid bacteria (LAB) suspension of 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 30 publications
1
10
1
2
Order By: Relevance
“…However, clinical trials overall are still very limited and therefore current evidence on probiotics, as weight loss agents are at most, suggestive. We also found no significant improvements in blood pressure although a recent study in animal models showed remarkable improvements in blood pressure after 8 week administration of Lactobacillus casei [ 19 ]. A recent meta-analysis by Khalesi et al from 9 clinical trials concluded that probiotic administration may modestly improve blood pressure, and the potency maybe enhanced if multiple species and strains are taken for more than 8 weeks [ 20 ].…”
Section: Discussioncontrasting
confidence: 59%
“…However, clinical trials overall are still very limited and therefore current evidence on probiotics, as weight loss agents are at most, suggestive. We also found no significant improvements in blood pressure although a recent study in animal models showed remarkable improvements in blood pressure after 8 week administration of Lactobacillus casei [ 19 ]. A recent meta-analysis by Khalesi et al from 9 clinical trials concluded that probiotic administration may modestly improve blood pressure, and the potency maybe enhanced if multiple species and strains are taken for more than 8 weeks [ 20 ].…”
Section: Discussioncontrasting
confidence: 59%
“…23,24 Moreover, a positive effect of probiotics for SHR with established hypertension in vascular protection and blood pressure control has already been described. 8,[24][25][26][27][28] Nonetheless, whether probiotics consumption is able to prevent the rise in blood pressure in mineralocorticoid-induced hypertension, and the possible role of SCFAs in this is still unknown. Bifidobacterium is commonly considered a beneficial bacterial genus and plays a critical role in the maturation and regulation of the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…They are non-pathogenic and non-spore-forming rods in morphology with the majority inhabiting the intestinal tract cavity. Currently, the genus Lactobacillus has been widely used as a probiotic source (Pringsulaka et al 2015) as it has several health-promoting effects and claims, such as improved gastrointestinal immune response (Christensen et al 2002), prevention of diarrhea (Biller et al 1995), treatment of colon cancer (Koop-Hoolithan 2001), attenuate hypertension (Yap et al 2016) and many others. Probiotic is designated by FAO/WHO (2002) as a live microorganism that offers health benefits to host cells when administered in sufficient quantity.…”
Section: Introductionmentioning
confidence: 99%